Implementasi Program Baca Tulis Al-Qur’an di Sekolah LHS ( Lima Hari Sekolah) untuk Meningkatkan Belajar Pendidikan Agama Islam Siswa SMP Negeri 2 Doko - Umi Nahdiyah; Nanang Zamroji (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
Implementation of the Al-Qur'an Reading and Writing Program in LHS Schools (FiveSchool Days) to Improve Islamic Religious Education Learning for Students of SMPN2 Doko. The purpose of this study is to obtain a description of how the implementation ofthe programread and write the Koran at SMPN 2 Doko. The field research category includes thisresearch qualitative. The method used to collect data through participant observation,documentation and in-depth interviews, conducting data analysis starting from reducingdata, presenting data, drawing conclusions. The validity of the data was tested by extendingpresence of researchers, triangulation, peer discussion and clarification with informants.The results of the research are the Al-Qur'an reading and writing program at SMPN 2 Dokohas been carried out and planned carefully with the school which is no longer included inlocal content but included in intra-school activities. Ottoman Method is the method used inthe Al-Qur'an reading and writing program in the learning process learning. Based on thelearning outcomes there are many significant developments related to the literacy programAl-Qur'an (BTQ), namely in reading it students can tartil, fluently and correctly based onmakhorijul letters, tajwid and the nature of the letters.